The Impact of Appearance Concerns on Depression and Anxiety in Rheumatoid Arthritis. (18th June 2012) - McBain, Hayley; Shipley, Michael; Newman, Stanton; ,
Abstract Objectives Increased levels of anxiety and depression are commonly reported by patients with rheumatoid arthritis (RA) in comparison to the general population. Rather than the clinical features of the disease, this difference has been attributed to psychosocial factors. Patients with RA can develop joint swelling and disfigurement as a direct result of the disease, and experience concerns about their altered appearance. This study aimed to identify if appearance‐specific issues contribute to our understanding of mood in RA, over and above demographic, functional and generalized psychosocial measures. Methods A total of 89 patients with RA completed a series of psychosocial questionnaires measuring demographics, physical function, general cognitive processes and a number of appearance‐specific concepts, to determine the contribution of appearance concerns to mood. Results Hierarchical linear regression suggested that living status, optimism, social support and appearance‐related social anxiety and avoidance are associated with levels of depression. The relationship between social support and depression was found to be mediated by appearance‐related social anxiety and avoidance. Optimism remained the only variable significantly associated with anxiety. Conclusion These findings confirm the role of optimistic cognitions and a supportive environment in determining the mood of patients with RA and also establishes a possible link between depression and appearance concerns in this population. Interventions targeting social support, optimism and social anxiety and avoidance in relation to appearance are key in the improvement of depression in this patient group. Copyright © 2012 John Wiley & Sons, Ltd.